Why does obesity cause diabetes? - Klein, Samuel; Gastaldelli, Amalia; Yki-Järvinen, Hannele; Scherer, Philipp E. (Cell metabolism, 2022)
The accumulation of an excessive amount of body fat can cause type 2 diabetes, and the risk of type 2 diabetes increases linearly with an increase in body mass index. Accordingly, the worldwide increase in the prevalence of obesity has led to a concomitant increase in the prevalence of type 2 diabetes. The cellular and physiological mechanisms responsible for the link between obesity and type 2 diabetes are complex and involve adiposity-induced alterations in β cell function, adipose tissue biology, and multi-organ insulin resistance, which are often ameliorated and can even be normalized with adequate weight loss. Klein et al. examine the cellular and physiological mechanisms that explain why people with obesity develop metabolic dysfunction and type 2 diabetes. They also review the effects of weight loss, induced by negative energy balance, on adipose tissue biology and multi-organ system function that can cause remission of diabetes.